1990
DOI: 10.1523/jneurosci.10-04-01388.1990
|View full text |Cite
|
Sign up to set email alerts
|

Increasing intracellular free calcium induces circumferential contractions in isolated cochlear outer hair cells

Abstract: The relationship between intracellular free calcium and the motile responses of outer hair cells isolated from the guinea pig cochlea was examined. Calcium levels were modulated by the addition of the calcium ionophores ionomycin or A23187 to the incubation medium and monitored with the fluorescent calcium indicator fluo-3. In the presence of 1.25 mM external calcium, the application of either ionophore (10 microM) led to an increase in intracellular free calcium from 157 +/- 76 nM to 1200 +/- 500 nM within 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
91
0
3

Year Published

1991
1991
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(109 citation statements)
references
References 34 publications
15
91
0
3
Order By: Relevance
“…Ionomycin at this concentration had no effects on hair-cell survival or morphology, suggesting that the concentration of Ca 2ϩ did not rise to an extreme level. Consistent with that conclusion, similar conditions raise intracellular Ca 2ϩ to only 1-2 M in cochlear hair cells (18).…”
Section: Resultssupporting
confidence: 80%
“…Ionomycin at this concentration had no effects on hair-cell survival or morphology, suggesting that the concentration of Ca 2ϩ did not rise to an extreme level. Consistent with that conclusion, similar conditions raise intracellular Ca 2ϩ to only 1-2 M in cochlear hair cells (18).…”
Section: Resultssupporting
confidence: 80%
“…In its role in efferent transmission, Ca 2ϩ enters through neuronal nicotinic ACh receptors to activate Ca 2ϩ -activated K ϩ channels, but the Ca 2ϩ signal will be primarily limited to the space between the cisternae and the plasma membrane. A third but incompletely understood role of Ca 2ϩ in outer hair cells is in regulating somatic electromotility (Dulon et al, 1990;Frolenkov et al, 2000;Beurg et al, 2001), which has been proposed as a mechanism for the slow efferent effects (Dallos et al, 1997;Sridhar et al, 1997). Is it possible there are large cytoplasmic transients in Ca 2ϩ produced by Ca 2ϩ -induced Ca 2ϩ release from the subsurface cisternae reminiscent of the sarcoplasmic reticulum in muscle (Saito 1983;Bannister et al, 1988)?…”
Section: Discussionmentioning
confidence: 99%
“…If Ca 2ϩ is mainly associated with control of motility, possibly a slow version (Dulon et al, 1990), neither the release mechanism nor mode of action of the divalent is properly understood. Nevertheless, it can be speculated that the large amount of endogenous calcium buffer will accelerate Ca 2ϩ transients, as it does in skeletal muscle, and also shield the subcellular organelles from large excursions in intracellular Ca 2ϩ occurring near the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patuzzi (2011) suggested that the Bounce is due to oscillations in outer hair cell (OHC) Ca 2+ levels as a result of the large AC component of the OHC receptor potential caused by low-frequency sound, which is less attenuated by OHC membrane filter properties. Ca 2+ controls the slow motility of OHCs (Dulon and Schacht 1992;Dulon et al 1990) and, as a consequence, cochlear amplifier activity. According to Patuzzi (2011), very LF sound should be the most effective in eliciting the Bounce as the AC component of OHC receptor potential is large, due to the low-pass filter properties of the OHC membrane.…”
Section: Introductionmentioning
confidence: 99%